Beef Producers' Risk Perceptions of an Agroterrorism Event Occurring in Oklahoma - Marcus A. Ashlock; D. Dwayne Cartmell II; James G. Leising (Journal of Applied Communications, 2012)
The purpose of this statewide study was to determine Oklahoma beef producers’ perceptions of the susceptibility of the state’s beef industry to a terrorist attack. Participants in this study were randomly selected from a population of 48,000 beef producers in this Oklahoma. All 470 respondents completed a telephone survey conducted by the Oklahoma Agricultural Statistics Service. Descriptive statistics, t-tests, and cross tabulations were used to analyze the data. Oklahoma beef producers perceived the beef industry was susceptible to an agroterrorism event, believed the feedlots to be at an elevated level of threat, were confident in their own operation’s biosecurity measures, believed their own operation was not susceptible to an agroterrorism event, and did not believe they had enough information about protection from terrorism to the beef industry.
Keywords: Agroterrorism; Agricultural Crisis; Beef Producer Risk Perception; Crisis Planning